FORSYTH-TECHNOLOGIES AS A TOOL FOR PROGNOSTICATION OF COMPANY DEVELOPMENT - Valentyna M. Shevchenko; Tatiana S. Mishustina; Alexandra A. Burtseva (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The article investigated the use of forsite-technologies as a tool for prognostication of the company development on the example of the «Biosphere» corporation. It has been established that over the years of research, the forsite methodology has incorporated dozens of traditional and fairly new expert methods. At the same time, their constant improvement takes place. The study uses a fast forsite technique, which allows you to obtain accurate prognosis in a short period of time. An analysis of the hygiene market shows that it is quite young and is actively developing. But economic and political instability greatly affects consumer ability and puts high demands on the image and positioning of companies in the market. Therefore, as part of this study, an assessment of the effectiveness of the Biosphere Corporation brand was made according to various expert methods, which corresponds to the principles of the forsite. A comprehensive assessment of the c effectiveness of the company’s brand was carried out according to various expert approaches, namely: based on the financial statements of the enterprise according to the methodology of the consulting company “Interbrand Group” (3.67 points); based on a survey of supporters loyal to the corporation’s brand, in accordance with the “Romir monitoring” methodology (4.59 points); based on management accounting indicators according to the V-RATIO brand listing methodology (4.2 points) and business assessment according to the WACC formula (3.0 points); which indicates the profitability of the company and the prospect of expanding its presence in other markets. It is noted that an important measure that will increase the profitability of invested equity is the improvement of the branding of Biosphere Corporation. Tactical solutions were proposed to promote and reformat the corporation’s own website on the Internet and a marketing budget was drawn up for the proposed measures. Forsite-technologies have been proven to be an effective tool for determining enterprise development priorities based on various expert approaches and allow you to evaluate events with a low probability, but with a large potential impact on the future of the area under study.